The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1038/srep35777
|View full text |Cite
|
Sign up to set email alerts
|

Optical manipulation of the alpha subunits of heterotrimeric G proteins using photoswitchable dimerization systems

Abstract: Alpha subunits of heterotrimeric G proteins (Gα) are involved in a variety of cellular functions. Here we report an optogenetic strategy to spatially and temporally manipulate Gα in living cells. More specifically, we applied the blue light-induced dimerization system, known as the Magnet system, and an alternative red light-induced dimerization system consisting of Arabidopsis thaliana phytochrome B (PhyB) and phytochrome-interacting factor 6 (PIF6) to optically control the activation of two different classes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“…[14] On the other hand, although theoretical calculations of band structures of perovskite materials have been widely performed for solving such open questions, there are serious differences in the calculated results, such as the effective mass of the hole varying between 0.12 and 0.36 m 0 (on average). [15][16][17][18][19][20] Therefore, the unexplained properties and physical origin of impressive solar-cell performances are still awaiting a direct experimental study of the band structures and the effective masses.…”
mentioning
confidence: 99%
“…[14] On the other hand, although theoretical calculations of band structures of perovskite materials have been widely performed for solving such open questions, there are serious differences in the calculated results, such as the effective mass of the hole varying between 0.12 and 0.36 m 0 (on average). [15][16][17][18][19][20] Therefore, the unexplained properties and physical origin of impressive solar-cell performances are still awaiting a direct experimental study of the band structures and the effective masses.…”
mentioning
confidence: 99%
“…In 2016, this model was constructed by com bining group theory with firstprinciples calculations. [134] Using both the valence and conduction bands' anisotropic gfactors, it is possible to estimate the difference between the electron and hole masses. Theoretical results for the exciton energies and the oscillator strength were produced as functions of the magnetic field.…”
Section: Magneto-optical Effectmentioning
confidence: 99%
“…Additionally, Heo and co‐workers demonstrated that Opto‐STIM1‐induced increased Ca 2+ concentrations in CA1 neuronal cells in the hippocampus are implicated in the reinforcement of context‐specific memory. The Sato group developed Ca 2+ optotools based on the Magnet and PhyB/PIF6 systems . For the Magnet‐based construct, pMagFast1 was fused with Gαq, and nMagHigh1 was localized at the plasma membrane through a CAAX motif.…”
Section: Figurementioning
confidence: 99%